2020
DOI: 10.26848/rbgf.v13.07.p3412-3427
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influence on the Leaf Morphoanatomical Characteristics of Myrcia splendens (Sw.) DC. (Myrtaceae)

Abstract: Myrcia splendens (Sw.) DC. is a native and endemic species of Brazil. Plants can have ecological plasticity due to environmental influences and studies on the ecological anatomy of leaves in the genus Myrcia DC. are scarce. In this sense, the present study aimed to verify the effect of seasonality and luminosity on the leaf morphoanatomical characteristics of Myrcia splendens (Sw.) DC., in order to contribute with information about the species responses to the natural abiotic factors of its occurrence. The bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(108 reference statements)
1
0
0
Order By: Relevance
“…Our results demonstrated that leaf anatomy changes aided in the guabiroba seedlings acclimation to total sunlight condition. In this treatment, the mesophyll (palisade and spongy parenchyma) thickness was responsible for the guabiroba leaf thickness; a similar effect has been observed in other Myrtaceae species (Da Costa et al, 2020;Moura et al, 2022). Inside sun leaves, palisade parenchyma contributes to the propagation efficiency and homogeneity of light, whilst spongy parenchyma promotes increases in the CO 2 diffusion (Barbosa-Campos et al, 2018;Karabourniotis et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…Our results demonstrated that leaf anatomy changes aided in the guabiroba seedlings acclimation to total sunlight condition. In this treatment, the mesophyll (palisade and spongy parenchyma) thickness was responsible for the guabiroba leaf thickness; a similar effect has been observed in other Myrtaceae species (Da Costa et al, 2020;Moura et al, 2022). Inside sun leaves, palisade parenchyma contributes to the propagation efficiency and homogeneity of light, whilst spongy parenchyma promotes increases in the CO 2 diffusion (Barbosa-Campos et al, 2018;Karabourniotis et al, 2021).…”
Section: Discussionsupporting
confidence: 72%